2017
DOI: 10.1137/16m1074187
|View full text |Cite
|
Sign up to set email alerts
|

iHDG: An Iterative HDG Framework for Partial Differential Equations

Abstract: Abstract. We present a scalable iterative solver for high-order hybridized discontinuous Galerkin (HDG) discretizations of linear partial differential equations. It is an interplay between domain decomposition methods and HDG discretizations, and hence inheriting advances from both sides. In particular, the method can be viewed as a Gauss-Seidel approach that requires only independent element-by-element and face-by-face local solves in each iteration. As such, it is well-suited for current and future computing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 45 publications
0
23
0
1
Order By: Relevance
“…From a linear algebra point of view, iHDG-I can be considered as a block Gauss-Seidel approach for the system (2) that requires only independent element-by-element and face-by-face local solves in each iteration. However, unlike conventional Gauss-Seidel schemes which are purely algebraic, the convergence of iHDG-I [45] does not depend on the ordering of unknowns. From the domain decomposition point of view, thanks to the HDG flux, iHDG can be identified as an optimal Schwarz method in which each element is a subdomain.…”
Section: Ihdg Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From a linear algebra point of view, iHDG-I can be considered as a block Gauss-Seidel approach for the system (2) that requires only independent element-by-element and face-by-face local solves in each iteration. However, unlike conventional Gauss-Seidel schemes which are purely algebraic, the convergence of iHDG-I [45] does not depend on the ordering of unknowns. From the domain decomposition point of view, thanks to the HDG flux, iHDG can be identified as an optimal Schwarz method in which each element is a subdomain.…”
Section: Ihdg Methodsmentioning
confidence: 99%
“…From the domain decomposition point of view, thanks to the HDG flux, iHDG can be identified as an optimal Schwarz method in which each element is a subdomain. Using an energy approach, we have rigorously shown the convergence of the iHDG-I for the transport equation, the linearized shallow water equation and the convection-diffusion equation [45].…”
Section: Ihdg Methodsmentioning
confidence: 99%
“…They concluded that both continuous and interior penalty discontinuous Galerkin algorithms with multigrid outperforms HDG with multigrid in terms of time to solution by a significant margin. One level Schwarz type domain decomposition algorithms in the context of HDG have been studied for elliptic equation [32,33], hyperbolic systems [36,37] and Maxwell's equations [34,35]. A balancing domain decomposition by constraints algorithm for HDG was introduced in [38] and studied for Euler and Navier-Stokes equations.…”
Section: A Brief Review On Solvers/preconditioners For Hdg Trace Systemmentioning
confidence: 99%
“…To that end, we take K = 0 in (1). Similar to [63,36], we consider the velocity field N p = 1 p = 2 p = 3 p = 4 p = 5 p = 6 6 178 137 107 92 79 73 7 * (10 −5 ) * (10 −8 ) 167 138 113 99 8 * (10 −2 ) * (10 −2 ) * (10 −2 ) * (10 −4 ) * (10 −5 ) * (10 −7 ) Table 3: Example II: number of ML-preconditioned GMRES iterations as the mesh and solution order are refined. N p = 1 p = 2 p = 3 p = 4 p = 5 p = 6 N p = 1 p = 2 p = 3 p = 4 p = 5 p = 6 The solution is shown in Figure 12(a) and the difficulty of this test case comes from the presence of a curved discontinuity (shock) emanating from the inflow to the outflow boundaries.…”
Section: Example Iii: Transport Equationmentioning
confidence: 99%
“…95,96 Concerning specific solution strategies for hybrid discretization methods, a parallel solver based on the iterative Schwarz method has been developed in, 97 fast multigrid solvers have been employed in [98][99][100] and iterative approaches inspired by the Gauss-Seidel method have been discussed in. 101,102 Moreover, tailored preconditioners for the hybrid DG method have been proposed in 103,104 in the context of the Stokes equations.…”
Section: Introductionmentioning
confidence: 99%